Strategies to Increase Competitiveness in Wisma Arimbi Yogyakarta - Supriyanto, Slamet (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The aim of the research is how to analyze the environment at Wisma Arimbi and what strategies to increase competitiveness at Wisma Arimbi Yogyakarta. The data analysis used in this research is descriptive qualitative. This writing aims to reveal facts, circumstances, phenomena, variables, and circumstances that occurred while the writing took place and present it as it is. From the results of the discussion, looking at the company's strengths, weaknesses, threats, and opportunities, a strategy can be obtained that can be implemented at Wisma Arimbi, namely an intensive competitive strategy with market penetration. With this strategy, Wisma Arimbi is expected to increase sales and income levels